The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1111/j.1365-2265.1995.tb02037.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of plasma adrenocortical steroids to low dose ACTH in normal subjects

Abstract: These results suggest that the sensitivity of secretion to physiological doses of ACTH in descending order is aldosterone > DHEA = cortisol. When peak and incremental values are used, sufficient doses of ACTH are 0.1 microgram for plasma aldosterone and 0.5 microgram for plasma cortisol and DHEA in the rapid ACTH test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
82
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 21 publications
13
82
2
Order By: Relevance
“…However, this test is labor intensive and contraindicated in some patients. The low-dose (1 mg) ACTH test has recently been introduced and proved to be sensitive in revealing partial adrenal insufficiency by providing physiological adrenocortical stimulation (5,6). The results of the low-dose (1 mg) ACTH test correlate closely with those of the reference test for the function of the HPA axis (7), and are superior to the standard (250 mg) ACTH test (8).…”
Section: Introductionmentioning
confidence: 69%
“…However, this test is labor intensive and contraindicated in some patients. The low-dose (1 mg) ACTH test has recently been introduced and proved to be sensitive in revealing partial adrenal insufficiency by providing physiological adrenocortical stimulation (5,6). The results of the low-dose (1 mg) ACTH test correlate closely with those of the reference test for the function of the HPA axis (7), and are superior to the standard (250 mg) ACTH test (8).…”
Section: Introductionmentioning
confidence: 69%
“…; s.c. injection with 2.5 mg (10) or even 4.0 mg (11) ACTH will cause no increase in plasma cortisol. Daidoh et al (12) found that 0.5 mg ACTH i.v. was the smallest dose that caused maximal stimulation of cortisol under normal conditions, starting with normal basal cortisol levels of about 200 nmol/l.…”
Section: Discussionmentioning
confidence: 99%
“…Preventing sodium accumulation by ACTH infusion into sodium-restricted subjects results in prolonged stimulation of aldosterone production (Tucci et al 1967). A sustained increase in THAldo excretion rate over four days of ACTH infusion has been reported (Pratt et al 1976), while more than one study has reported that levels of plasma aldosterone are more sensitive to ACTH stimulation than either cortisol or DHEA (Kem et al 1975;Daidoh et al 1995). Biglieri found aldosterone to be within the normal range -but not increased -in Cushing's syndrome (Biglieri et al 1963).…”
Section: Association Of 11-hydroxylation Efficiency With Hypertensionmentioning
confidence: 99%